2018
DOI: 10.1590/rbz4720160419
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of beef cattle production from tropical pastures

Abstract: -The live weight gain of cattle on tropical pastures is reviewed and found to be low and dependent on the length of the growing season. Supplements may be added to address the primary limiting nutrient, which, in the dry season, is crude protein. The response relationships of live weight gain to level of supplement (protein or energy) that have been developed for animals on pasture in Brazil and Australia have been compared and found to be very similar. This gives confidence in recommending a supplementation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 17 publications
(27 reference statements)
3
43
1
7
Order By: Relevance
“…This claim would argue against the logic of raising heifers on pastures such as Bd (Experiment 3), usually assigned to fattening steers that provide higher short-term financial returns. This view coincides with that expressed by Poppi et al (2018) to the effect that under some conditions, a minimalist approach to feeding grazing cattle may be economically optimal; this argument may explain the popularity of low input tropical pastures among ranchers in some regions.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…This claim would argue against the logic of raising heifers on pastures such as Bd (Experiment 3), usually assigned to fattening steers that provide higher short-term financial returns. This view coincides with that expressed by Poppi et al (2018) to the effect that under some conditions, a minimalist approach to feeding grazing cattle may be economically optimal; this argument may explain the popularity of low input tropical pastures among ranchers in some regions.…”
Section: Discussionsupporting
confidence: 76%
“…On the contrary, strategies that keep females in marginal nutritional conditions are certain to result in low lifetime production as shown above. Depending upon economic conditions and farmers´ preferences (Poppi et al 2018), supplementation of cattle grazing these tropical pastures would be expected to increase their performance. Several studies conducted in the Brazilian Cerrado have unequivocally shown a positive response of fattening cattle grazing Brachiaria-based pastures to energy and protein supplements (da Silva-Marques et al 2018a, 2018bNeves et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under this production system, animals are usually subject to periods of food scarcity due to seasonal patterns of rainfall and, consequently, seasonal variation of pasture quality and availability. Depending on the severity of the dry season, the animals can be subject to seasonal weight loss if no supplementation is provided, this being a major constraint to beef cattle production in the tropics [4, 5]. However, supplementation is costly, and a more effective strategy would be to select cattle that are less sensitive to environmental variation in unfavorable environments and more adapted to harsh conditions.…”
Section: Introductionmentioning
confidence: 99%